Mantle of Mindscape; Cocoon for Creativity… an art studio (SIRJANĀ – A Journal Of Arts and Art Education, 2017)
When we contemplate on one particular motif that artists have depicted the most through the ages in their artworks, human anatomy spontaneously comes to mind. However, there is one component the artists have incorporated in their artworks more than human anatomy and that is the space. Be it abstract, figurative or realistic, without space art cannot exist. Science and technology show that humans have taken a giant leap in terms of their progress and advancements. Earth is getting smaller by the second and the land it provides is never enough. However, we have learnt tricks to multiply it. The horizontal landscapes are getting occupied with vertical houses and skyscrapers. We need more space. And in all this concrete haphazard urbanizations, what does space means for an artist? The internal space which is cultivated from imaginations and memories and the external space that s/he greatly wants to balance with the internal, it all is indeed a gigantic metaphorical continuum. They perhaps need solitude, to reconcile with this idea of the space that has come into being from the unification of the internal and the external. And yet again, through the ages, they have been getting hold of themselves in a very important space which they call their studio. A brief comparative observation here attempts to unfold how art studios down the line has evolved with changing times in the west and more importantly in Nepal.